Pengambilan Kembali Logam Litium dan Cobalt dari Baterai Li-Ion dengan Metode Leaching Asam Sitrat - Yuliusman Yuliusman (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Batteries are often used in mobile phones is a type of battery Li-Ion or Lithium Ion Battery (LIB). Cobalt and lithium used in batteries is important metal that is often used in various fields. Batteries that are not used become hazardous waste. Metal recovery from waste batteries is one solution to maintain the availability of raw materials of lithium and cobalt. In this study the recovery of lithium and cobalt was done with leaching method, which dissolves metals from the waste battery into the leaching agent. Citric Acid (C6H8O7) was used as the leaching agent, because it is one of the organic acids that can be used in the leaching process lithium. The results showed that the metal content in batteries LIB 35.30 ppm lithium metal and 408.55 ppm cobalt metal. The concentration of leaching agent take effect on the percentage of leaching. The optimum operating conditions for the leaching process is at a concentration of citric acid of 1.5 M; with a contact time of 30 minutes and a temperature of 55 ° C.  In these conditions, the optimum percentage was obtained for the leaching of metal lithium and cobalt are 98.08% and 86.28%, respectively, respectively.